2000
DOI: 10.1080/10473289.2000.10463998
|View full text |Cite
|
Sign up to set email alerts
|

Distance-Weighted Traffic Density in Proximity to a Home Is a Risk Factor for Leukemia and Other Childhood Cancers

Abstract: Occupational exposure to elevated concentrations of benzene is a known cause of leukemia in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
161
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(168 citation statements)
references
References 16 publications
3
161
1
3
Order By: Relevance
“…Elevated risks of childhood cancer were associated with several surrogate measures of vehicle exhaust exposure, including traffic volume, car density, estimated concentration of nitrogen dioxide in outdoor air and proximity to sources of vehicle exhaust (Savitz and Feingold, 1989;Knox and Gilman, 1997;Nordlinder and Jarvholm, 1997;Feychting et al, 1998;Harrison et al, 1999;Pearson et al, 2000). Recent studies in California evaluating childhood cancer and traffic density have generally found no association (Reynolds et al, 2001;Langholz et al, 2002;Reynolds et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated risks of childhood cancer were associated with several surrogate measures of vehicle exhaust exposure, including traffic volume, car density, estimated concentration of nitrogen dioxide in outdoor air and proximity to sources of vehicle exhaust (Savitz and Feingold, 1989;Knox and Gilman, 1997;Nordlinder and Jarvholm, 1997;Feychting et al, 1998;Harrison et al, 1999;Pearson et al, 2000). Recent studies in California evaluating childhood cancer and traffic density have generally found no association (Reynolds et al, 2001;Langholz et al, 2002;Reynolds et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nuisances perception at home was also suggested as a good proxy for traffic -related air pollution in Switzerland (Oglesby et al, 2000 ). Following the same rationale as the VESTA ''traffic density'' index, some studies combined traffic and distance data (Wilkinson et al, 1999;Pearson et al, 2000). In a recent case -control study of air pollution from traffic and childhood cancer, two cumulated exposure indices were also accommodated, as in the present study, with the same Danish OSPM software that is built in the ExTra model (Raaschou -Nielson et al, 2000;RaaschouNielson et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Continuous long-term exposure to low environmental concentrations of benzene is an issue of special public health concern, as several investigations so far reported positive associations between residence near potential hydrocarbon emission sources (e.g., oil raffineries) or indicators of automotive emissions and acute childhood leukaemia (Knox, 1994;Lyons et al, 1995;Sans et al, 1995;Knox and Gilman, 1997;Harrison et al, 1999;Wilkinson et al, 1999). Moreover, five out of six case-control studies showed a positive association between different indicators of air pollution or heavy traffic in the vicinity of children's homes and acute leukaemia (Savitz and Feingold, 1989;Nordlinder and Jarvholm, 1997;Feychting et al, 1998;Harrison et al, 1999;Pearson et al, 2000;Raaschou-Nielsen et al, 2001;Langholz et al, 2002;Crosignani et al, 2004), whereas in three of these studies, this association turned out to be significant (Nordlinder and Jarvholm, 1997;Pearson et al, 2000;Crosignani et al, 2004).…”
Section: Introductionmentioning
confidence: 99%